Improved Transparent Gas Sensor Properties of Cu-Doped SnO2 Films using O2 Plasma Treatment - N Somjaijaroen; R Sakdanuphab; A Sakulkalavek (My University, 2019)
Abstract Cu-doped SnO 2 films were deposited on glass slide substrate using an RF magnetron sputtering method. The effects of O 2 partial pressures in the deposition process and post O 2 plasma treatment were assessed for optical and sensing properties. O 2 partial pressures from 2% to 10% were assessed. Post-plasma treatment used a 15 mL/min O 2 flow, 450 °C annealing temperature and 30 min treatment time. Optical transmission spectra showed that the films deposited at higher O 2 partial pressures had higher transparency and increased band gaps from 3.08 to 3.78 eV. After O 2 plasma treatment, the films showed better than optical transmission. However, when the O 2 partial pressure increased to 10%, the optical transmission declined slightly because the film had higher surface roughness, smaller crystals and fewer oxygens in the parent rutile tetragonal cells, enhanced the sensor response at room temperature.
Keywords: Partial pressure; Rutile; Tetragonal crystal system; Gas Sensing Nanomaterials and Sensors